SYNERGISTIC EFFECT OF GINGER, PROPOLIS ADDED TO CONCENTRATED DIET ON SOME PRODUCTION AND PHYSIOLOGICAL CHARACTERISTICS OF THE AWASSI EWES - AL-jubori, O. S. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was aimed to find out the synergistic effect of ginger and propolis some productivity and physiological traits of Awassi ewes. The study was conducted in field the Department of Animal Production - College of Agriculture, University of Baghdad Al-Jaderia, during 14/01/2016 - 03/27/2016, using 12 Awassi ewes with ages from 9 -11 months old ,average weight of 31 kg, The results showed a significant increase in the glucose for concentration (P